IDENTIFIKASI FAKTOR-FAKTOR YANG MEMENGARUHI REMAJA BERMAIN ROLE PLAYING GAME PADA SMARTPHONE - SUARTAMA, I GEDE ARY; SUCIPTAWATI, NI LUH PUTU; ASIH, NI MADE (E-Jurnal Matematika, 2019)
This research is aimed to determine the factors that influence teenagers playing Role Playing games (RPG) games using factor analysis. Sample of this study were 120 respondents. The respondents were teenager aged 16 years to 24 years who like to play RPG games. The data were obtained from primary sources using questionnaires distributed using Google form. The results showed there were three factors that influence teenagers playing RPG games. Those factors are : 1)The interest and satisfaction when playing the game, 2) Quality of the smartphone and friends, and 3) The quality of internet. The cumulative percentage of the three factors is able to explain 67.34% of the total variable.